Membangun Budaya Hukum dalam Pengelolaan Sampah untuk Lingkungan Berkelanjutan - Ruminingsih; Aguk Nugroho; Mokh Tho’if; Achmad Wildan D; Dhyan Purwitarini; Muhari Muhari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Waste-related issues have become increasingly complex environmental challenges as a result of population growth and shifting consumption patterns within society. Although Indonesia has established a legal framework through Law Number 18 of 2008 on Waste Management, its implementation at the community level continues to encounter various obstacles, particularly low legal awareness and an underdeveloped legal culture. This community service program aims to foster and strengthen a legal culture in waste management as an effort to promote environmental sustainability in Mrutuk Village, Widang District, Tuban Regency. The activities were conducted using participatory and descriptive approaches, including legal education, dissemination of waste management regulations, reinforcement of legal substance and enforcement structures, and community-based assistance. The results demonstrate an improvement in public understanding and awareness of the importance of managing waste in accordance with legal provisions, a shift in attitudes from compliance motivated by supervision toward voluntary compliance, and the emergence of community initiatives to actively engage in environmentally oriented waste management. Therefore, strengthening legal culture has proven to be a crucial instrument in encouraging environmentally responsible behavior and supporting the achievement of sustainable development.